Plasticization of bacterial poly(3-hydroxybutyrate) - Ceccorulli, Giuseppina; Pizzoli, Maria; Scandola, Mariastella (Macromolecules, 1992)
Many bacteria accumulate poly(3-hydroxybutyrate) (P(3HB)) as an intracellular carbon and energy-reserve material in the form of granules. The fact that P(3HB) macromolecules are enzymically accessible in the granules in vivo but do not serve as a substrate to intracellular depolymerase after granule drying has been the subject of much debate. The aim of this work is to contribute to the intriguing subject of P(3HB) mobility, through investigation of the plasticization phenomenon. The effect of increasing amounts of a biodegradable plasticizer, di-n-butyl phthalate (DBP), on the glass transition of P(3HB) has been examined over the whole range of concentrations, from pure polymer to pure diluent. The influence of DBP on crystallization kinetics and melting of P(3HB) will be discussed elsewhere.